Monitoring the quality of the visitor experience: An evolutionary journey. (March 2019) - Pearce, Joanna; Dowling, Ross
Abstract: Due to the dual mandate often associated with parks and protected areas of providing conservation of natural and cultural resources as well as providing opportunities for recreation, managers have often looked for differing ways to measure the quality of the visitor experience. Professor Susan Moore with the help of her colleagues, has been at the forefront of research into the visitor experience, and this paper provides a summary of this work. From measuring the perceptions of visitors to national parks, to examining ways of improving the measurement of visitor satisfaction, and making the transition to measuring and reporting on loyalty, Sue's work was always theoretically grounded and applicable to managers. Her work has tracked the evolution of visitor management and it is now essential this work continue so researchers and managers can improve their understanding and continue to build connections with visitors who hold protected areas in high regard.